2007
DOI: 10.3748/wjg.v13.i6.889
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ-glutamyltransferase, alanine aminotransferase, and aspartate aminotransferase activity in Iranian healthy blood donor men

Abstract: AIM:To determine serum γ-glutamyltransferase (GGT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) activity, and to assess their correlation with demographic and clinical findings in healthy blood donors. METHODS:This cross-sectional study was performed in 934 male blood donors, aged 18 to 68 years, who consecutively attended Tehran blood transfusion service in 2006. All participants were seronegative for HBV or HCV infections, non alcohol users, and all underwent a standard interview and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
3
14
2
Order By: Relevance
“…We found that the average BMI of patients with HA was 29.8, similar to that obtained in other studies of BMI levels around 27-30 (12). Furthermore, in the multivariate analysis in our study we observed a statistically significant association between the patient's BMI and the presence of AH, an increase of 12.5% in the probability of AH for each point increase in BMI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the average BMI of patients with HA was 29.8, similar to that obtained in other studies of BMI levels around 27-30 (12). Furthermore, in the multivariate analysis in our study we observed a statistically significant association between the patient's BMI and the presence of AH, an increase of 12.5% in the probability of AH for each point increase in BMI.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms that the majority of increases above normal values for transaminases are mild, often below twice the normal range. Several studies claim that AH is associated with an increased risk of developing cardiovascular disease, hypertension, diabetes and dyslipidemia (12). In our study, despite significant percentage of patients with these diseases among those with AH (28.8% of hypertensives, diabetics 18.2% and 33.3% of patients with dyslipidemia), no association was found statistically significant among these factors and the presence or persistence of AH, after carrying out a multivariate analysis controlling other variables.…”
Section: Discussioncontrasting
confidence: 68%
“…However, it is known that men represent the majority of blood donors with reactive serology, with prevalence ranging from 76% to 84% [21][22] . The average age of 37 years-old is similar to that described by other authors, ranging between 34 and 41 years-old [23][24] . Higher mean age in this study was independently associated with seropositivity for viral hepatitis.…”
Section: Conflict Of Interest Referencessupporting
confidence: 87%
“…Similarly, no significant associations between GGT and age, BMI and anthropometric measurements as substantiated by the works of Giral et al [15]. However, Khedmat et al [1] were of contrary opinion. In their works, there was a highly significant association between GGT and age, BMI, blood pressure, serum lipids and lipoproteins.…”
Section: Discussionmentioning
confidence: 90%
“…The health benefits of screening for fatty liver and other components of the metabolic syndrome seems as necessary as performing tests for viral hepatitis B and C infections on the blood donors [1]. This is because an estimated 1% -9% of people who have no symptoms are known to have high liver enzyme levels attributable to non alcoholic fatty liver disease whose risk factors have been known to be obesity, diabetes (insulin resistance), hyperlipidaemia and hypertension [2].…”
Section: Introductionmentioning
confidence: 99%